2016
DOI: 10.1007/s00392-016-0995-8
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and the holidays

Abstract: Christmas and Independence day were associated with increased heart failure admissions immediately following the holidays. The holidays themselves saw lower admission rates. Overeating on holidays, associated emotional stressors, lesser exercise and postponing medical around holidays may be among the factors responsible for the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…First, accesss to validated, high-quality, electronic medical records [22] provided a large sample size and large number of cardiovascular events, reflected real-life conditions, and warranted high external validity. Moreover, the large sample size allowed us to constrict the study period avoiding periods with higher rate of cardiovascular hospitalizations, such as Christmas [55], and thus avoiding violation of the SCCS assumption of constant events along time. Second, by using the self-controlled case series design, we automatically controlled for all time-fixed individual level factors that could be related to the association between outdoor temperature and human health, such as socioeconomic status [56] or body fat [26].…”
Section: Discussionmentioning
confidence: 99%
“…First, accesss to validated, high-quality, electronic medical records [22] provided a large sample size and large number of cardiovascular events, reflected real-life conditions, and warranted high external validity. Moreover, the large sample size allowed us to constrict the study period avoiding periods with higher rate of cardiovascular hospitalizations, such as Christmas [55], and thus avoiding violation of the SCCS assumption of constant events along time. Second, by using the self-controlled case series design, we automatically controlled for all time-fixed individual level factors that could be related to the association between outdoor temperature and human health, such as socioeconomic status [56] or body fat [26].…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al 69. evaluated the impact of winter season and holidays in 22 727 HF patients; the authors demonstrated that Christmas and Independence Day were associated with increased HF admissions immediately after the holidays, suggesting overeating, emotional stressors, lesser exercise, and postponing medicals around holidays as possible causes.…”
Section: With Heart Failure Present: Exercise Improvement With Trainimentioning
confidence: 99%
“…Overeating, emotional stress, and reduced physical activity are factors related to increased heart failure events during Christmas holidays [ 33 ]. Hypertension is the most common recurring factor in MetS [ 34 ] and an independent risk factor for cardiovascular diseases and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%